Ez Prep Concentrate (Ez Prep) Sebagai Alternatif Reagen Deparafinasi Pada Pewarnaan Hematoksilin Eosin - Apriani; Andrianus; Stephanie Marisca; Patricia Diana (G-Tech: Jurnal Teknologi Terapan, 2023)
Xylol is a deparaffinizing agent that is commonly used in each deparaffinization step in tissue histology staining. However, due to its high toxicity and high price, efforts have been made to find alternatives that are safer and cheaper. Ez Prep concentrate is one of the most commonly used deparaffinizing agents in Ventana Medical Systems, Inc (Ventana) devices. This product is designed for use as a BenchMark Series automated slide stainer. Besides being cheaper than xylol, its toxicity is also low. It is necessary to prove the effectiveness of the EZ Prep concentrate reagent so that it can be used as an alternative to xylol. This research is experimental in nature and will be carried out from September to November 2022 at the Siloam Hospital Lippo Village Anatomical Pathology Laboratory. The sample used is myoma and breast tissue. The results showed that all samples deparfined with EZ prep concentrate gave good quality microscopic results (score 3). Thus, EZ Prep concentrate can be considered as a substitute for xylol